2017
DOI: 10.1016/j.celrep.2017.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Modifications of Histone H3K9 Promote Binding of CHD3

Abstract: Chromatin remodeling is required for genome function and is facilitated by ATP-dependent complexes, such as the nucleosome remodeling and deacetylase (NuRD). Among its core components is chromodomain helicase DNA binding protein 3 (CHD3) whose functional significance is not well established. Here, we show that CHD3 co-localizes with other NuRD subunits, including HDAC1, near H3K9ac-enriched promoters of NuRD target genes. The tandem PHD fingers of CHD3 bind histone H3 tails and posttranslational modifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 59 publications
(84 reference statements)
0
35
0
Order By: Relevance
“…The polarization measurements were acquired with a Tecan Infinite M1000 Pro plate reader by exciting at 470 nm and measuring polarized emission at 519 nm with 5nm excitation and emission bandwidths. The fluorescence polarization was calculated from the emission polarized parallel and perpendicular to the polarized excitation light as described previously (23,24). The data were then fit to a noncooperative binding isotherm to determine the dissociation constants.…”
Section: Methodsmentioning
confidence: 99%
“…The polarization measurements were acquired with a Tecan Infinite M1000 Pro plate reader by exciting at 470 nm and measuring polarized emission at 519 nm with 5nm excitation and emission bandwidths. The fluorescence polarization was calculated from the emission polarized parallel and perpendicular to the polarized excitation light as described previously (23,24). The data were then fit to a noncooperative binding isotherm to determine the dissociation constants.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that JMJD2A is highly expressed in a variety of tumours and is involved in the regulation of cancer cell proliferation, survival and conversion between glycolysis metabolism and mitochondrial oxidation . However, several researches show that histone H3 demethylase JMJD2A drives tumorigenesis and H3k9me3 was reduced in several cancers . In particular, regulating H3K9me3 activity contributes to cancer progression .…”
Section: Discussionmentioning
confidence: 99%
“…66 However, several researches show that histone H3 demethylase JMJD2A drives tumorigenesis 65,[67][68][69][70][71] and H3k9me3 was reduced in several cancers. 72,73 In particular, regulating H3K9me3 activity contributes to cancer progression. 74 In fact, our present findings indicate miR-24-2 accelerates hepatocarcinogenesis by inhibiting JMJD2A and increasing H3K9me3.…”
Section: Discussionmentioning
confidence: 99%
“…It allowed for detailed analysis of the multivalent engagement of the PSIP1 PWWP domain and the PHF1 Tudor domain with the nucleosome containing H3K C 36me3 67,68 . Similarly, it helped establish the mechanism of the BRDT bromodomain binding to the NCL generated H4K5acK8ac nucleosomes and enabled characterization of how paired readers, the tandem PHD fingers of CHD4 and CHD3, bind to unmodified nucleosomes 62,64,69 .…”
Section: The Effect Of Nucleosome Nature On Histone Tail Bindingmentioning
confidence: 99%
“…A large number of reader domains have now been identified including methyl-lysine binding chromodomains, PHD fingers, Tudor and PWWP domains, and acetyl-lysine binding bromodomains 9,10,13,65 . The structural basis of these interactions have been extensively characterized using correspondingly modified histone peptides, but are only recently being characterized in the context of the nucleosome [61][62][63][64][66][67][68][69] . Interestingly, several histone reader domains have now been found to associate not only with histone tails but also with nucleic acids [70][71][72] .…”
Section: The Effect Of Nucleosome Nature On Histone Tail Bindingmentioning
confidence: 99%